PENGEMBANGAN MEDIA PEMBELAJARAN KOMIPA PADA MATA PELAJARAN PKN DI KURIKULUM MERDEKA KELAS IV BERBASIS APLIKASI CANVA FOR EDUCATION - Febby Rahmanda; Muhammad Sofwan (P2M STKIP Siliwangi, 2024)
This research aims to (1) To describe the procedure for developing komipa learning media in Civics subjects in the Grade IV Independent Curriculum based on the Canva for Education application, (2) to determine the level of validity of Kompipa learning media in Civics subjects in the Grade IV Independent Curriculum based on applications. canva for education, (3) to determine the level of practicality of the komipa learning media in Civics subjects in the fourth-grade independent curriculum based on the canva for education application. This research uses research and development methods using the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) development model. The results of this research and development are in the form of komipa learning media for class IV in Civics learning based on the Canva for education application. The validation results by material experts obtained a validity score of 80 in the valid category, the validation assessment results from media experts obtained a validity score of 68 in the quite valid category and the results of the validation assessment by language experts obtained a validity score of 96.3 in the very valid category. The practicality of the komipa learning media that has been developed has also passed the assessment of expert practitioners who received a score of 100 in the very practical category. The practicality of komipa media also pays attention to the student response questionnaire in the small group trial which obtained a score of 90 and in the large group trial which obtained a score of 89.46. Based on the results of this research, it can be concluded that the Komipa learning media for Civics subjects in the Grade IV Independent Curriculum based on the Canva for Education application is valid and very practical and very suitable for use as a Civics learning medium for Grade IV Elementary Schools.